A Dam Good Argument - Delf, Liz; Drummond, Rob; Kelly, Kristy (Open textbook library., 2022)
Arguments are all around us. Everywhere we look, someone is trying to get our attention, change our minds, or sell us something. Learning about how persuasion works will make you a more thoughtful and skeptical consumer of all that content, so that you can come to your own conclusions and recognize the underlying assumptions that inform those attempts to persuade you. This book is about analyzing others' arguments and crafting your own. The rhetorical choices that you make as a writer–from evidence to structure to tone–impact how your audience will receive your ideas. Using those tools effectively will help your voice be heard.